A Rapid Quantitative Assay of Factor VIII (AHG) Without the Use of Haemophilia A Plasma - Jung, Ernst G. (Thrombosis and Haemostasis, 1960)
A new method for the quantitative determination of factor VIII (AHG) without using haemophilia A plasma as test substrate has been described. The comparison to Geiger et al. shows a good concordance. The normal range of factor VIII in adults is 50—150% (normal plasma taken as 100%) and the average value of healthy newborns is 78%. This is compared to the average values of the other clotting factors in newborns. Factor VIII is not affected by deficient vitamin K resorption.